Emotions and self-efficacy toward simple machines learning through a STEM practice - Muñoz-Losa, Aurora; Marcos-Merino, José María (Frontiers in Education, 2024)
IntroductionThis study explores the impact of an interactive physics class on the emotions and self-efficacy of elementary education students, specifically in their future roles as educators using STEM-based pedagogical methods. The research aims to understand how such an approach affects students’ emotional responses and confidence in teaching STEM topics.MethodsThe sample included 97 fourth-year prospective elementary teachers. Participants completed pretests and posttests measuring emotions and self-efficacy related to both course content and the pedagogical approach.ResultsFindings indicated a significant increase in both positive emotions and self-efficacy following the interactive class. Male students reported higher levels of positive emotions and self-efficacy than their female peers. Furthermore, students with backgrounds in sciences and technology showed greater improvement compared to those from social science backgrounds. A positive correlation between emotions and self-efficacy was observed.DiscussionThe manipulative, collaborative, and interdisciplinary nature of the physics class likely contributed to the observed positive changes in emotions and self-efficacy. Network analysis suggested that reducing boredom could enhance emotional responses, given its role in affecting both positive and negative emotions. On the other hand, it has been observed that uncertainty could be beneficial in STEM activities due to their relationship with self-efficacy.